Trust as a signal of a social norm and the hidden costs of incentive schemes - Dirk Sliwka (Institute for the Study of Labor (IZA), 2006)
An explanation for motivation crowding-out phenomena is developed in a social preferences framework. Besides selfish and fair or altruistic types a third type of agents is introduced: These 'conformists' have social preferences if they believe that sufficiently many of the others do too. When there is asymmetric information about the distribution of preferences (the 'social norm'), the incentive scheme offered or autonomy granted can reveal a principal's beliefs about that norm. High-powered incentives may crowd out motivation as pessimism about the norm is conveyed. But by choosing fixed wages or granting autonomy the principal may signal trust in a favorable social norm.
Keywords: 330; Anreizvertrag; Soziale Norm; Vertrauen; Soziale Wohlfahrtsfunktion; Agency Theory